Heat stabilizer modified ceramic powder for PVC (polyvinyl chloride) plate
By adsorbing organic tin into the pores of ceramic powder and wrapping it with chlorinated paraffin, the problem of easy migration and volatility of organic tin in PVC sheet production is solved, and its use efficiency and thermal stability in PVC materials are improved, and its use is extended. Lifespan avoids product discoloration and mechanical performance degradation.
Patent Information
- Application Number
- CN202411312774.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2024-12-13
AI Technical Summary
In the production process of PVC sheets, the organic tin heat stabilizer used is easy to migrate and volatilize, causing it to consume too quickly, fail to fully exert its efficacy, and it is difficult to effectively prevent product discoloration and mechanical properties.
Modify ceramic powder with heat stabilizer. By adsorbing organic tin into the pores of the ceramic powder and wrapping the organic tin modified ceramic powder with chlorinated paraffin, it improves its fluidity and stability in PVC materials and prevents organic tin. The specific process includes mixing, calcining, crushing, grinding and vacuum drying.
It effectively reduces the loss of organic tin, significantly improves its use efficiency and thermal stability in PVC materials, avoids product discoloration and mechanical properties, and extends the service life of organic tin.
Smart Images

Figure CN119119583A_ABST
Abstract
Description
[0001] This application is a divisional application. The application date of the original application is April 29, 2024. The application number is 2024105244345. The name of the invention is: A method for producing PVC sheets. Technical Field
[0002] The invention relates to a heat stabilizer modified ceramic powder for PVC plates. Background Art
[0003] In the production process of PVC sheets, hydrogen chloride will be decomposed during the processing, resulting in product discoloration and a decrease in the mechanical properties of the product. In order to prevent the decomposition of PVC during the processing, a heat stabilizer needs to be added. Organic tin is widely used because of its good use effect. However, since organic tin is mainly liquid, it is easy to migrate and volatilize when used in PVC processing, and it is consumed too quickly, resulting in large waste, and it does not really play its full role. How to improve the use efficiency of organic tin has become a need. Summary of the invention
[0004] In order to improve the utilization efficiency of organic tin, the present application proposes a production method of PVC sheet, wherein the production raw material formula includes the following components by weight: 100 parts of PVC resin powder, 5-9 parts of thermal stabilizer modified ceramic powder, 2-4 parts of processing aid, 4-5 parts of polyester plasticizer, 3-4 parts of toughening agent, 40-55 parts of calcium carbonate, and 30-35 parts of secondary aluminum ash;
[0005] The production method comprises the following steps:
[0006] (1) stirring the components to form a raw material mixture;
[0007] (2) adding the raw material mixture into an extruder for extrusion;
[0008] (3) The extruded melt is cooled to room temperature through a shaping die to obtain a PVC sheet.
[0009] The processing aid is specifically an acrylic ester copolymer, and the toughening agent is specifically chlorinated polyethylene.
[0010] Specifically, the thermal stabilizer modified ceramic powder is prepared by the following method:
[0011] The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and a binder are mixed, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is at least one of bentonite, tetraethyl orthosilicate and polyvinyl alcohol;
[0012] (1.2) crushing and grinding the granular ceramic sintered body to obtain ceramic powder;
[0013] (1.3) Immerse the ceramic powder in liquid organic tin, stir evenly, and dry at 60-70°C for 3-4 hours to obtain organic tin modified ceramic powder, in which the organic tin content is 20-30wt%, and then mix chlorinated paraffin with the organic tin modified ceramic powder to prepare thermal stabilizer modified ceramic powder; the volume ratio of organic tin to ceramic powder is (1-2):1, and the volume ratio of chlorinated paraffin to organic tin modified ceramic powder is (0.8-1.5):1. The organic tin is specifically dibutyltin dilaurate, di-n-octyltin dilaurate, dibutyl bismaleate or isooctyl tin dimethylthioacetate. In step (1.2), the granular ceramic is ground by a vertical mill.
[0014] In the present application, the pores in the ceramic powder are used to adsorb the organic tin in the ceramic powder to reduce the loss of the organic tin, and the organic tin modified ceramic powder is wrapped with chlorinated paraffin to improve the fluidity of the thermal stabilizer modified ceramic powder in the material and avoid agglomeration. Since the organic tin is adsorbed in the pores of the ceramic powder, the organic tin will not migrate or volatilize during the production process and processing of the PVC material, and its long-term and efficient thermal stability can be more significantly exerted.
[0015] Specifically, in step (1.1), the mass ratio of secondary aluminum ash, silica, kaolin, montmorillonite and binder is (70-80):(10-15):(1-5):(3-8):(1-5).
[0016] If the amount of secondary aluminum ash added is too low, the Al2O3 content in the ceramic will be too low, and the porosity in the ceramic powder will be too low, which will affect the penetration of organic tin in the ceramic powder and reduce the adsorption performance of organic tin. When the amount of secondary aluminum ash added is high, the strength of the resulting ceramic powder is poor.
[0017] Specifically, in step (1.1), the calcination process is as follows: first, the temperature is increased to 600-650°C at a rate of 8-12°C / min, then the temperature is increased to 900-1000°C at a rate of 3-6°C / min, and the temperature is kept at that temperature for 1-2 hours, then the temperature is cooled to room temperature, and then the temperature is increased to 1300-1350°C at a rate of 8-12°C / min, and the temperature is kept at that temperature for 1-3 hours.
[0018] After the temperature reaches 600-650℃, AlN and metallic aluminum in the secondary aluminum ash begin to oxidize. Too fast a heating rate can easily cause expansion and cracking of the ceramic body. At a lower heating rate, the full oxidation of AlN and metallic aluminum can be guaranteed. After the oxidation of AlN and metallic aluminum is completed, the structure of the ceramic sintered body is basically formed. After cooling to room temperature, the temperature is raised to 1300-1350℃ again, and during the insulation process, it gradually reaches the ceramic phase, so that the ceramic sintered body can expand rapidly and produce cracks inside, so that it can be split into irregular particles in the subsequent crushing and grinding process, which is beneficial to the adsorption of organic tin.
[0019] When the temperature is lower than 1300℃, the strength of the ceramic will be too low, the ceramic body will be easy to break, and the pores inside the ceramic body will be easily damaged, which is not conducive to storing more organic tin. When the temperature is higher than 1350℃, excessive casting will occur, reducing the number of pores in the ceramic body. Under the above conditions, the porosity of the formed ceramic powder is 40-52%. The secondary aluminum ash also contains a certain amount of cryolite. During the sintering process of the ceramic, the cryolite and aluminum nitride in the secondary aluminum ash will produce gas, which is more conducive to the formation of porous materials in the ceramic.
[0020] Specifically, in step (1.2), the granular ceramic sintered body is crushed and ground, and then sieved with a 400-500 mesh screen, and the sieved material is taken as ceramic powder. Under the above particle size, while ensuring that the formed thermal stabilizer modified ceramic powder can pass through the screw extruder smoothly with other components of the plastic, the ceramic powder can also absorb more organic tin. If the particle size of the ceramic powder is too large, it will cause difficulty in discharging the extruder.
[0021] Furthermore, in order to remove the air in the ceramic powder as much as possible and increase the adsorption amount of organic tin, in step (1.3), the vacuum degree is 20-100Pa absolute pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the 1# ceramic powder prepared in Example 1.
[0023] Figure 2 This is another SEM image of the 1# ceramic powder prepared in Example 1.
[0024] Figure 3 This is the EDS spectrum of 1# ceramic powder prepared in Example 1.
[0025] Figure 4 This is the X-ray diffraction pattern of the 1# ceramic powder prepared in Example 1. DETAILED DESCRIPTION
[0026] Example 1
[0027] Preparation of 1# thermal stabilizer modified ceramic powder:
[0028] (1.1) The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder are mixed with a high-speed mixer, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is specifically bentonite. The mass ratio of secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder is 75:12:3:6:4. The drying temperature is 120°C, the drying time is 3h, and the calcination process is as follows:
[0029] The temperature was first increased to 620°C at a rate of 10°C / min, then slowly increased to 950°C at a rate of 4°C / min, kept at this temperature for 1.5 h, then cooled to room temperature, and then increased to 1320°C at a rate of 10°C / min, and kept at this temperature for 2.5 h.
[0030] (1.2) The granular ceramic sintered body is crushed and ground by a vertical mill and sieved by a 400-mesh screen, and the material under the screen is taken as 1# ceramic powder. The porosity of 1# ceramic powder is 48%. The SEM image obtained when testing the ceramic powder in this embodiment is as follows: Figure 1 and Figure 2 The obtained EDS spectrum is shown in Figure 3 The obtained X-ray diffraction pattern is shown in Figure 4 shown.
[0031] (1.3) Under a vacuum state of 90 Pa absolute pressure, the ceramic powder is immersed in organic tin, stirred evenly, and dried at 60° C. for 4 hours to obtain organic tin modified ceramic powder, in which the organic tin content is 25wt%, and then chlorinated paraffin and the organic tin modified ceramic powder are mixed and stirred to prepare 1# thermal stabilizer modified ceramic powder; the volume ratio of organic tin to ceramic powder is 1.5:1. The volume ratio of chlorinated paraffin to organic tin modified ceramic powder is 1:1, and the organic tin is specifically di-n-octyltin dilaurate.
[0032] The production of PVC sheets, the production raw material formula includes the following components by weight:
[0033] 100 parts of PVC resin powder, 6 parts of 1# heat stabilizer modified ceramic powder, 3 parts of processing aid, 4 parts of polyester plasticizer, 3 parts of toughening agent, 45 parts of calcium carbonate, 35 parts of secondary aluminum ash; the processing aid is specifically an acrylic copolymer, the toughening agent is specifically chlorinated polyethylene, and the mesh number of the secondary aluminum ash is 700-800 mesh.
[0034] The production method comprises the following steps:
[0035] (1) stirring the components to form a raw material mixture;
[0036] (2) 2) The raw material mixture is added into a twin-screw extruder for extrusion. The temperature of each zone of the twin-screw extruder is: Ⅰ (conveying section) 200℃ Ⅱ (melting section) 190℃ Ⅲ (metering section) 180℃ Ⅳ (die head) 185℃.
[0037] (3) The extruded melt is pressed and formed by a calender, and then peeled and cooled to room temperature to obtain a PVC sheet.
[0038] In this embodiment, the chemical composition (dry basis) of the secondary aluminum ash is as follows (mass percentage):
[0039] Element <![CDATA[Al2O3]]> MgO <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> Cl <![CDATA[Na2O]]> CaO F AlN other content 58.87 2.73 10.46 2.74 2.45 2.23 2.19 2.16 12.13 4.04
[0040] Example 2
[0041] Preparation of 2# thermal stabilizer modified ceramic powder:
[0042] (1.1) The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder are mixed with a high-speed mixer, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is specifically bentonite. The mass ratio of secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder is 70:15:3:7:5. The drying temperature is 100°C, the drying time is 3h, and the calcination process is as follows:
[0043] The temperature was first increased to 650°C at a rate of 9°C / min, then slowly increased to 960°C at a rate of 5°C / min, kept at this temperature for 1.5 h, then cooled to room temperature, and then increased to 1330°C at a rate of 10°C / min, and kept at this temperature for 2.5 h.
[0044] (1.2) The granular ceramic sintered body is crushed and ground by a vertical mill and sieved by a 450-mesh screen, and the material under the sieve is taken as 2# ceramic powder. The porosity of 2# ceramic powder is 44%.
[0045] (1.3) Under a vacuum state of 30Pa absolute pressure, the ceramic powder is immersed in organic tin, stirred evenly, and dried at 70°C for 3 hours to obtain organic tin modified ceramic powder, in which the organic tin content is 27wt%, and then chlorinated paraffin and organic tin modified ceramic powder are mixed and stirred to prepare 2# thermal stabilizer modified ceramic powder; the volume ratio of organic tin to ceramic powder is 2:1. The volume ratio of chlorinated paraffin to organic tin modified ceramic powder is 1.2:1. The organic tin is specifically dibutyl tin monobutyl bismaleate.
[0046] The production of PVC sheets, the production raw material formula includes the following components by weight:
[0047] 100 parts of PVC resin powder, 7 parts of 2# heat stabilizer modified ceramic powder, 2 parts of processing aid, 4.5 parts of polyester plasticizer, 3.5 parts of toughening agent, 40 parts of calcium carbonate, 30 parts of secondary aluminum ash; the processing aid is specifically an acrylic copolymer, the toughening agent is specifically chlorinated polyethylene, and the mesh size of the secondary aluminum ash is 600-700 mesh.
[0048] The production method comprises the following steps:
[0049] (1) stirring the components to form a raw material mixture;
[0050] (2) Add the raw material mixture into a twin-screw extruder for extrusion; the temperature of each zone of the twin-screw extruder is: Ⅰ (conveying section) 190℃ Ⅱ (melting section) 180℃ Ⅲ (metering section) 170℃ Ⅳ (die head) 175℃.
[0051] (3) The extruded melt is pressed and formed by a calender, and then peeled and cooled to room temperature to obtain a PVC sheet.
[0052] In this embodiment, the chemical composition (dry basis) of the secondary aluminum ash is as follows (mass percentage):
[0053] Element <![CDATA[Al2O3]]> MgO <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> Cl <![CDATA[Na2O]]> CaO F AlN other content 65.67 3.25 9.24 2.23 2.44 2.35 1.45 2.37 9.08 1.92
[0054] Example 3
[0055] Preparation of 3# thermal stabilizer modified ceramic powder:
[0056] (1.1) The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder are mixed with a high-speed mixer, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is specifically bentonite. The mass ratio of secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder is 75:11:5:5:4. The drying temperature is 120°C, the drying time is 1.5h, and the calcination process is as follows:
[0057] The temperature was first increased to 640°C at a rate of 10°C / min, then slowly increased to 1000°C at a rate of 6°C / min, kept at this temperature for 1 hour, then cooled to room temperature, and then increased to 1350°C at a rate of 11°C / min, and kept at this temperature for 3 hours.
[0058] (1.2) The granular ceramic sintered body is crushed and ground by a vertical mill and sieved by a 400-mesh screen, and the sieved material is taken as 3# ceramic powder. The porosity of 3# ceramic powder is 50%.
[0059] (1.3) Under a vacuum state of 60Pa absolute pressure, the ceramic powder is immersed in organic tin, stirred evenly, and dried at 65°C for 3.5 hours to obtain organic tin modified ceramic powder, in which the organic tin content is 30wt%, and then chlorinated paraffin and the organic tin modified ceramic powder are mixed and stirred to prepare 3# thermal stabilizer modified ceramic powder; the volume ratio of organic tin to ceramic powder is 2:1. The volume ratio of chlorinated paraffin to organic tin modified ceramic powder is 1.5:1. The organic tin is specifically dibutyltin dilaurate.
[0060] The production of PVC sheets, the production raw material formula includes the following components by weight:
[0061] 100 parts of PVC resin powder, 9 parts of 3# heat stabilizer modified ceramic powder, 4 parts of processing aid, 5 parts of polyester plasticizer, 4 parts of toughening agent, 55 parts of calcium carbonate, 32 parts of secondary aluminum ash; the processing aid is specifically an acrylic copolymer, the toughening agent is specifically chlorinated polyethylene, and the mesh size of the secondary aluminum ash is 400-600 mesh.
[0062] The production method comprises the following steps:
[0063] (1) stirring the components to form a raw material mixture;
[0064] (2) Add the raw material mixture into a twin-screw extruder for extrusion; the temperature of each zone of the twin-screw extruder is: Ⅰ (conveying section) 195℃ Ⅱ (melting section) 185℃ Ⅲ (metering section) 175℃ Ⅳ (die head) 180℃.
[0065] (3) The extruded melt is pressed and formed by a calender, and then peeled and cooled to room temperature to obtain a PVC sheet.
[0066] In this embodiment, the chemical composition (dry basis) of the secondary aluminum ash is as follows (mass percentage):
[0067] Element <![CDATA[Al2O3]]> MgO <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> Cl <![CDATA[Na2O]]> CaO F AlN other content 67.73 1.75 8.03 3.12 2.65 2.86 1.75 2.31 7.68 2.12
[0068] Comparative Example 1
[0069] This comparative example 1 is basically the same as example 1, except that the heat stabilizer modified ceramic powder is replaced by organotin chlorinated paraffin, the amounts of organotin solution and chlorinated paraffin contained in the heat stabilizer modified ceramic powder are the same as those in the heat stabilizer modified ceramic powder, and no ceramic powder is added.
[0070] Thermal stability test:
[0071]
[0072] It can be seen from the above that the thermal stabilizer-modified ceramic powder of the present application can effectively improve the thermal stability of the PVC material.
Claims
1. A heat stabilizer modified ceramic powder for PVC sheets, It is characterized in that Prepared by the following method: (1.1) secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and a binder are mixed, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is at least one of bentonite, tetraethyl orthosilicate and polyvinyl alcohol; (1.2) crushing and grinding the granular ceramic sintered body to obtain ceramic powder; (1.3) Immersing ceramic powder in liquid organotin, stirring evenly, and drying at 60-70°C for 3-4 hours to obtain organotin-modified ceramic powder, in which the organotin content is 20-30wt%, and then mixing chlorinated paraffin with the organotin-modified ceramic powder to prepare thermal stabilizer-modified ceramic powder; the volume ratio of organotin to ceramic powder is (1-2):1, and the volume ratio of chlorinated paraffin to organotin-modified ceramic powder is (0.8-1.5):
1.
2. The production method according to claim 1, It is characterized in that In step (1.1), the mass ratio of secondary aluminum ash, silica, kaolin, montmorillonite and binder is (70-80):(10-15):(1-5):(3-8):(1-5).
3. The production method according to claim 1, It is characterized in that In step (1.1), the roasting process is as follows: First, increase the temperature to 600-650℃ at a rate of 8-12℃ / min, then increase the temperature to 900-1000℃ at a rate of 3-6℃ / min, keep warm for 1-2h, then cool to room temperature, and then increase the temperature to 1300-1350℃ at a rate of 8-12℃ / min, and keep warm for 1-3h.
4. The production method according to claim 1, It is characterized in that In step (1.2), the granular ceramic sintered body is crushed and ground, and then sieved with a 400-500 mesh sieve, and the sieved material is taken as ceramic powder.
5. The production method according to claim 1, It is characterized in that In step (1.3), the ceramic powder is immersed in liquid organic tin under vacuum, and the vacuum degree is 20-100Pa absolute pressure.
Citation Information
Patent Citations
Low-smoke flame-retarding ceramizable PVC material, preparation method, and application thereof
CN107286518A
Porous ceramic heat storage ball and method for preparing porous ceramic heat storage ball based on secondary aluminum ash
CN115537556A
Information processing apparatus, transfer position correction method, and substrate processing apparatus
KR1020220164422A
METHOD OF PRODUCING Mn-Bi BASED SINTERED MAGNET AND Mn-Bi BASED SINTERED MAGNET THEREFROM
KR1020230052805A
